Tumor Microenvironment Profiling Identifies Prognostic Signatures and Suggests Immunotherapeutic Benefits in Neuroblastoma - Feng, Chenzhao; Li, Ting; Xiao, Jun; Wang, Jing; Meng, Xinyao; Niu, Huizhong; Jiang, Bin; Huang, Lei; Deng, Xiaogeng; Yan, Xueqiang; Wu, Dianming; Fang, Yifan; et al. (Frontiers in Cell and Developmental Biology, 2022)
Tumor microenvironment (TME) influences disease initiation and progression. Cross-talks within TME can affect the efficacy of immunotherapies. However, a precise, concise and comprehensive TME landscape in neuroblastoma (NB) has not been established. Here, we profiled the TME landscape of 498 NB patients on a self-curated gene list and identified 3 prognostic TMEsubgroups. Differentially expressed genes (DEGs) among 3 TMEsubgroups constructed a genetic background of the TME landscape and characterized 3 GeneSubgroups. The Subgruop with the worst overall survival prognosis, TMEsubgroup/ GeneSubgroup3, lacked immune cell infiltration, received the highest scores of MYCN- and ALK-related signatures and lowest scores of immune pathways. Besides, GeneSubgroup3 would benefit from anti-GD2 therapies instead of anti-PD-1. We further created a 48-gene signature, the TMEscore, to infer prognosis and validate it in 3 independent NB cohorts and a pan-cancer cohort of 9460 patients. We did RNA-seq on 16 samples and verified that TMEscore was higher in stage 3/4 patients than stage 1/2. The TMEscore could also predict responses for several immunotherapies. After adding clinical features, we found that the nomogram-based score system, the TMEIndex, surpassed the current COG risk system at predicting survivals. Our analysis explained TME at the transcriptome level and paved the way for immunotherapies in NB.